New Challenges for Sustainable Rural Development in the 21st Century (part 4) - Lorber, Lučka (Journal for Geography, 2010)
The relation between rural and urban areas differs widely through the World. In some areas, particularly in Europe, the distinction between rural and urban is becoming increasingly blurred. This regards in particular rural areas close to urban centres where a process of integration of rural and urban space is taking place. Thus many rural areas, while benefiting from an increased interaction with the urban areas close by and/or from an increasingly diversified economic base, also face the challenges of losing their rural characteristics and identity. At the same time more remote rural areas with low population density and a difficult economic development face an increasing dichotomy between rural and urban areas. Over the next decade urban agglomerations will benefit from current economic and demographic trends whereas many remote rural areas face increasing difficulties and needs to better capitalise their territorial potential.